Importance of Applying Modern Information Technologies and Pedagogical Technologies to the Educational Process (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
It is difficult to imagine the development of a developing society without information technologies, especially computers. The field of information and communication technologies is one of the rapidly developing and rapidly developing areas of human activity. The Ministry of Higher Education, Science and Innovations of the Republic of Uzbekistan pays great attention to the issue of informatization of the education system. One of the main tasks of the National Program for Personnel Training is to improve the quality of education. This article provides information on the importance of applying modern information technologies and methods of implementing pedagogical technologies in the educational process.